Low-cost and high-performance 3D printed YBCO superconductors. Issue 1 (1st January 2021) - Mendes, Diogo; Sousa, David; Cerdeira, Ana C.; Pereira, Laura C.J.; Marques, Ana; Murta-Pina, João; Pronto, Anabela; Ferreira, Isabel
Abstract: High-performance YBCO 123 (YBa2 Cu3 O7-x ) bulk superconductor samples were produced using the 3D printing paste-extrusion technique. The YBCO powder obtained after sintering a pre-mixture of Y2 O3, BaCO3 and CuO powders at 950 °C was used in the formulation of pastes for extrusion in a 3D freeform printer. The 3D samples printed from pastes containing the pre-mixture powders were sintered, while those produced using the YBCO powder were not. X-ray diffraction (XRD), energy dispersive spectroscopy (EDS) and Raman analysis all confirmed the YBCO phase after sintering, both in the powder and in the samples made with the pre-mixture. Scanning electron microscopy (SEM) images revealed powder grains of heterogeneous size and geometry, as well as grain aggregation, in the sintered samples. Superconducting quantum interference device (SQUID) measurements taken within a fixed magnetic range revealed that the printed pieces have a typical magnetization temperature of 92 K, reaching −1.43 emu/g and −1.59 emu/g respectively a zero-field-cooled magnetization (ZFC) for sintered and non-sintered printed samples.